Dielectric properties of Agaricus bisporus slices relevant to drying with microwave energy. Issue 1 (1st January 2020) - Jiang, Ning; Liu, Chunquan; Li, Dajing; Lagnika, Camel; Zhang, Zhongyuan; Huang, Jiapeng; Liu, Chunju; Zhang, Min; Yu, Zhifang
ABSTRACT: Dielectric properties of sliced Agaricus bisporus samples, with 0.16–0.89 [g/g, wet basis (w.b.)] moisture content, were determined using a network analyser and an open-ended coaxial-line probe, over a frequency range of 915 MHz to 2450 MHz and a temperature range of 25°C to 60°C. The results showed that the permittivity of A. bisporus was a function of frequency, moisture content, and temperature. The dielectric constant and loss factor were directly proportional to moisture content and temperature, respectively, and both decreased with increasing frequency. However, the influence of temperature on the dielectric constant showed a different trend, as this was affected by the moisture content of the sample. The dielectric loss factor initially increased and then decreased with the decrease in moisture content. Both inflection points appeared at the moisture content value of 0.69 (g/g, w.b.), which represents the "semi-bound water transfer" point. Third-degree polynomial models could be used to describe dielectric constant and loss factor values as functions of moisture content and temperature. The penetration depth decreased with increasing frequency and temperature; however, this first decreased with decreasing moisture content and then increased. Notably, the penetration depth was at a low ebb when the moisture content ranged from 0.69 to 0.52 (g/g, w.b.), indicating easier uneven drying. Low frequency (915 MHz) with large penetration depth represents a highly effective method for large-scale industrial dielectric microwave drying of A. bisporus slices from the angle of uniformity.